The Correlation between Self-Efficacy and Writing Achievement of Undergraduate Students - Gisella, Indri; Roni, Rusman; Mulyadi (Jurnal Pendidikan Tambusai, 2021)
The recent study aimed to find out the correlation between self-efficacy and writing achievement of undergraduate students of English education study program at PGRI university of Palembang. In this study, 24 students of seventh semester were chosen as sample through purposive sampling. This study applied correlation research design. The data were collected by using questionnaires and tests, and they were analyzed by using Pearson product moment correlation coefficient, simple and multiple regression analysis. The results showed that the sig value of correlation between self-efficacy and writing achievement was 0.00 which was lower than 0.05, with 59.8% contribution of self-efficacy. It indicated that there was significant correlation between self-efficacy and writing achievement. Since the Pearson Correlation value was 0.773, it indicated strong correlation between self-efficacy and writing achievement.